Trabekuloplasti pada Glaukoma: Sebuah Tinjauan Pustaka Terkini - Lily, Lia Listya; Kalangi, Geraldi Marcelino; Manufandu, Gracea Sintike; Anugrahsari, Santi (Universitas Kristen Krida Wacana, 2024)
Glaucoma is a progressive optic neuropathy that can lead to irreversible blindness, where intraocular pressure (IOP) serves as the only modifiable risk factor for disease control. Among the various treatment modalities, laser trabeculoplasty, especially Selective Laser Trabeculoplasty (SLT), has gained popularity as it improves aqueous humor outflow and reduces IOP. This review combines recent studies comparing SLT with other modalities such as Micropulse Laser Trabeculoplasty (MLT) and their clinical outcomes. The purpose of thisliterature review is to highlight the efficacy of Selective Laser Trabeculoplasty (SLT) in managing intraocular pressure (IOP)in glaucoma patients, especially primary open angle glaucoma (POAG), both as first-line therapy and as adjunctive therapy. Literature sources were selected through an internet search using articles in research journal databases on Google Scholar and Pubmed and 30 literatures were selected from these methods. The literature revealed that SLT, as a first-line therapy or adjunct to medical treatment, effectively lowers IOP and can be repeated safely with continued efficacy. In addition, SLT offers an alternative for patients who are unresponsive to topical treatment, providing a non-invasive optionthat may eliminate the need for surgery. This review also examines the role of SLT in long-term glaucoma management, its comparison with newer techniques, and the effectiveness of repeated treatments in maintaining IOP control. Further studies are recommended to validate the long-term outcomes of SLT, especially for various applications and its comparison with newer laser therapies.